PEOPLE PLEASER DALAM FILM BOLEHKAH SEKALI SAJA KUMENANGIS: ANALISIS SEMIOTIKA ROLAND BARTHES - Rediva Hany Fathonah; Samsurrohman Samsurrohman (JURNAL ILMIAH PENELITIAN MAHASISWA, 2025)
The film "Bolehkah Sekali Saja Kumenangis " (May I Cry Once) depicts people-pleaser behavior through the character Tari, wich is characterized by self-sacrifice, conflict avoidance, and emotional suppression to maintain harmonious social relationships. This behavior is normalized through values ​​of politeness, obedience, and self-sacrifice, particularly in the context of women. This research investigates how people-pleaser behavior is represented and the social myths formed through this film. This research employed a qualitative method with a Roland Barthes semiotic approach, encompassing denotation, connotation, and myth analysis. Data were obtained from observations of film scenes depicting submissiveness, emotional suppression, and conflict avoidance, and were supported by literature review. The results indicate that the film portrays people-pleaser behavior as a form of politeness and maturity in accordance with ideal feminine standards, thus making self-sacrifice an accepted social norm. These results confirm that people-pleaser behavior is not simply an individual issue but a social construct reproduced through film.